의료급여관리사의 재가전환관리 경험 - 황윤희; 이가언; Hwang, Yunhee; Lee, Gaeon (Journal of Korean Academy of Nursing, 2023)
Purpose: This phenomenological study tried to understand the essence of the transitional care experience of medicaid case managers and its structural meaning. In addition, it was attempted to establish a system of transitional care and seek support measures for medicaid case managers. Methods: The participants of this study were 7 medicaid case managers who had spent more than 1 year and 6 months in medicaid pilot project. Data were collected with individual in-depth interviews from June to December 2021. The data were analyzed by Giorgi's phenomenological analysis method. Results: The seven constituents derived from the results of this study were 'struggle to establish a living environment', 'dedication to supporting independent living', 'anxiety about safety', 'pressure on care responsibilities', 'distress in building the pilot project', 'pride in role', and 'expectation for improvement'. Conclusion: The study results provide a comprehensive understanding of the transition care reality for medicaid case managers. They also shed light on managers' perceptions and attitudes. These findings can serve as fundamental information for establishing support measures for medicaid case managers and transitional care systems.